All digital low-cost NICAM modulator based on modern DSP technology - Korud, Andriy; Korud, Vasyl (Видавництво Львівської політехніки, 2011)
Structure, algorithms and implementations details of the NICAM 728 modulator introduced in the article. Although such solutions already exists, the prqooserf modulator was designed from scratch, with low-cost, tow-power and high integration requirements in mind. Proposed ADPLL clock generation let achieve required frequency stability without TCXO.
Keywords: DSP; modulation; FPGA; DOS; DSP; modulacja; FPGA; DDS